Menanamkan Spiritual Leadership di Era Milenial untuk Membangun Jiwa Kepemimpinan - Margaretha Taniria Sarumaha; Sariyatun Sariyatun; Susanto Susanto (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This study aims to provide an effort in the Millennial Era in terms of leadership by instilling Spiritual Leadership values. This is because the millennial era is an agent of change and is also the spearhead of the leadership relay in building this nation's civilization. The approach used in this research is a library research approach. This approach is carried out by examining theories, concepts and principles related to the discussion. While data collection is done by document study techniques, namely data obtained from the relevant literature. The data were analyzed by qualitative descriptive analysis, in which all the collected data will be analyzed systematically. The results showed that Spiritual Leadership as a fundamental aspect of motivation from an action and behavior in the effectiveness of building a leadership spirit in the Millennial Era. Because, Spiritual Leadership contains exemplary, service, integrity, love, and divine values in goals, processes, culture and attitudes that are very much needed in the Millennial Era in responding to technological challenges.